Andalucia and the Republican Educational Project: Building of Schools and Dignifaying Actions of Teacher´s Role: The Case of Granada (1931-1933) - Canalejo Alonso, Silvia (Hispania Nova, 2021)
The aim of this article is to study the mechanisms used in order to improve the quality of education in Granada that the first republican government managed and their impact on the province in the context of an obsolete and strongly rural Andalucia. In the presence of such scene due to a high rate of illiteracy, the main courses of action stablished were the building of new educative centres and the adaptation of school infrastructure, as well as the improving of professional conditions in teachers with the intention of dignifying their work and the teaching-learning system itself. The use of primary sources, specially archive ones, has been essential to find out how the changes in education were able to transform the educational reality in the province of Granada.
Keywords: first republican biennium; illiteracy; schools; teachers; salaries